Information handling in logistics management - DRB Oriental Honda as a case study / Roslan Ahmad - Ahmad, Roslan (2002)
Logistics Management these days is a key point of success in some business dealing. Logistics Management today has been fully equipped with new technology facilities such as Information and Communication Technology"(ICT), update logistics facilities such as air transportation, sea transportation and land transportation and the skill-full professional staff's or workers who handle the job responsibilities. The emergence of JCT in logistics management business has increased the capability and deliverables results to the customers. Automotive Manufacturing business as an example has used JCT in their logistics business dealing with customers, suppliers and alliances. Effective and efficient strategic planning in an organization is important to drive the future and survival of the company. A part of the plan is by improving the Logistics Management area which focused more on customer needs. Deliverables of product to customer within specific period of time, effective communication with suppliers and alliances and efficient logistics operation towards daily operation activities can only be successful by implementing and enhancement of Information Handling in Logistics Management. Logistics Management these days is all about strategic planning, information, communication, knowledge workers, up to date facilities and transportation systems and also creativity.